MORAL VALUE IN THE HISTORY TEXT BOOK (ANALYSIS OF THE TEXTBOOK OF HISTORY OF INDONESIA CLASS X) - Ratmelia, Yeni (JURNAL PENDIDIKAN ILMU SOSIAL, 2018)
This article analyzes the moral values contained in compulsory history textbooks in class X. Textbooks are the dominant instructional medium (instructional) of the role in the class, media of curriculum materials, and the central part of an educational system. The formation of character or character of the child can be done through three frameworks, namely the moral knowing, moral feeling, and moral behavior. Thus, the result of the formation of a child's character attitude can be seen from three aspects, namely moral concepts, moral attitudes, and moral behavior. In analyzing this discourse using qualitative method is considered appropriate to be used as research base for a researcher.